TEUKU NYAK MAKAM AND HIS ROLE IN THE DUTCH COLONIAL WAR ON THE EAST COAST OF ACEH (1865-1896) - Rachmatsyah Rachmatsyah; Tengku Sahudra (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
Teuku Nyak Makam was a prominent warlord on the East coast of Aceh in defending sovereignty from Dutch interference. In addition, the front guard of the Tamiang, Langkat and Deli regional bases. In an important role, he delegated troops under Teuku Muhammad in Seuruway (1885), and was assisted by the Warlords Umar and Nyak Ulim to blockade the Dutch patrol in Tamiang until 1895. In July 1896 Teuku Nyak Makam returned to Aceh Besar and ended his struggle being arrested in Lamnga. The discussion; Teuku Nyak Makam actively defended Aceh's sovereignty against the Dutch colonials; In addition to opposing Dutch colonialism in Aceh Tiga Sagi, also on the East Coast of Aceh; then Teuku Nyak Makam succeeded in consolidating troops on the East Coast. This study uses historical analysis methods, namely transcripts, books, historical monuments/relics. The first is data reduction, namely the selection process, simplification. The second presentation of data, obtained in the form of a story that is systematic and easy to understand and understand. The three systematic analyzes are in accordance with the formulation of the problem presented. The results of his research that Teuku Nyak Makam succeeded in coordinating the Acehnese troops against the Dutch on the coast of East Sumatra from various leadership wings; Teuku Muhammad and Teuku Tapa conducted operations on the battlefield along the East coast in 1889. In June 1891 they were able to break the Dutch patrol troops in Seuruway (1895), and blockade the Dutch troops.